Voice of Automatic Translation Work Versus Transcreation Work - Silvia Qatrinnada; Kristi Nuraini (Journal La Sociale, 2024)
This study aims to find out the correlation between automatic translation work and transcreation work in translating some messages. Particularly in the context of style when translating from Indonesian to English. The analysis focuses on the relationship between translation procedures and the type of adaptation in translation. This study uses qualitative methods and descriptive analysis to explain the meaning in translation and transcreation in order to see advantages and disadvantages from automatic translation and transcreation for better understanding the different perspectives. Findings show that the data from Google Accelerator Playbook found eight translation procedures proposed by Newmark, which includes word-for-word translation, Literal Translation, Naturalization, Transposition, Descriptive Equivalent, Modulation, Cultural Equivalent and Transference. The discussion and analysis of the translation procedures related to the concept of transcreation and adaptation that generally affect the meaning of target language. However, the concept and type of adaptation in the transcreation are still equivalent to the applied translation procedures. The results show that there is a correlation between automatic translation and transcreation in particular context and type. This process is to omit any translation errors in the translation tool and create an accurate translation of the source text by seeing the concept of the transcreation process.